Manifestations of metabolic syndrome after hypertensive pregnancy - Pouta, Anneli; Hartikainen, Anna-Liisa; Sovio, Ulla; Gissler, Mika; Laitinen, Jaana; McCarthy, Mark I; Ruokonen, Aimo; Elliott, Paul; Järvelin, Marjo-Riitta (Hypertension (Dallas, Tex. 1979), 2004)
Small follow-up studies of hospital-based series indicate women with preeclampsia have an increased risk of insulin resistance postpartum. However, long-term data are lacking among women with gestational hypertension without proteinuria. Using a general population-based sample of 5889 women from Northern Finland followed longitudinally since birth in 1966, we examined these associations and the influence of the subject's own birth weight and gestational age on this relationship. At age 31, blood pressure was measured and blood samples collected from 2678 women, of which 1463 women had had at least 1 singleton pregnancy. Of these, 45 had been hospitalized because of gestational hypertension and 49 because of preeclampsia. Women who had had either gestational hypertension or preeclampsia during their first pregnancy (average age 25 years) had increased blood pressure at 31 years compared with women with previous normotensive pregnancy, even after adjustment for body mass index (P<0.001 in gestational hypertension, P=0.023 in preeclampsia group). When compared with the whole female population, women with previous gestational hypertension at same age still had higher blood pressure, while this difference was weaker for women with previous preeclampsia. Women with gestational hypertension and preeclampsia also had higher waist circumference, waist/hip ratio, and body mass index, as well as increased serum insulin levels and lower glucose/insulin ratio than women with previous normotensive pregnancy. The associations remained after adjustment for participant's own birth weight or gestational age. Women born before gestational week 37 had a 2-fold risk for gestational hypertension in their first pregnancy (RR: 2.53; 95% CI: 1.0, 6.2).